Pengaruh fanatisme terhadap agresivitas simpatisan partai politik di Kabupaten Bima yang dimoderasi oleh altruisme - Asikin, Muhammad Taufik; Ari Firmanto (Universitas Muhammadiyah Malang, 2024)
During the election period, as well as before and after, there were numerous controversies, one of which involved conflicts between political party sympathizers, including those that occurred in Bima Regency. This conflict was identified as an act of aggression. Aggressiveness often arises from the high levels of fanaticism held by individuals or political party sympathizers. The aim of this research is to examine how fanaticism influences the aggressiveness of political party sympathizers in Bima Regency, with altruism as a moderating factor. The research employed quantitative correlational methods, using data analysis techniques such as moderated regression analysis. Three scales were used in this study: the Buss-Perry Aggression Questionnaire (BPAQ), a fanaticism scale, and an altruism scale. The results showed a significant influence of fanaticism on aggressiveness (p<0.005; β = 0.398). However, the second result indicated that altruism did not moderate the relationship between fanaticism and aggressiveness (p>0.005; β = -0.009). The implication of the research is that political party sympathizers should avoid excessive fanaticism to prevent aggressive behavior.